Foote was first! : how one curious woman connected carbon dioxide and climate change - Bryant, Jen, 1960- (Quill Tree Books, an imprint of HarperCollins Publishers, 2026)
From award-winning author Jen Bryant and bestselling illustrator Amy June Bates comes the incredible true story of STEMinist Eunice Foote, the woman who discovered the science behind global warming. From a young age, Eunice Foote's natural curiosity led her to learn more about how the world worked. What makes milk turn to butter? Why can I see my breath when it's cold? Why are there different kinds of clouds? By the time she grew up, scientists announced that the Earth was much hotter in the past, and that the warmer temperatures must mean the Earth's core was the cause. But Eunice thought something else could be at work. Through experiments and tests, Eunice's curiosity helped her make an important breakthrough: the greenhouse effect. Jen Bryant and Amy June Bates have created a remarkable biography about Eunice Foote, the first person to discover that trapped carbon dioxide warms the Earth's surface--a process that causes climate change, which impacts the world to this day.